Job quality and poverty in Latin America. Issue 4 (14th September 2018) - Brummund, Peter; Mann, Christopher; Rodriguez‐Castelan, Carlos
Abstract: Labor market dynamics have played a significant role in the remarkable social gains experienced in the recent past across Latin America. Assessing quality of employment, beyond the perspective of income, to include other fundamental aspects of jobs – such as whether jobs are secure, provide benefits, or are satisfying – can shed light on the sustainability of these achievements. This is particularly pertinent given the region's current economic slowdown. Using harmonized data for 15 countries in Latin America, this paper connects the role of job quality with the recent process of inclusive growth across the region, and particularly with how individuals worked their way out of poverty. The paper first proposes a multi‐dimensional measure for job quality, and then uses this measure to compare job quality across countries and over time. The paper also studies correlates of job quality and the relationship between job quality and poverty. One main finding is that job quality across the region began to increase in 2003. The best predictors of job quality are age, gender, firm size, formal employment, and union membership. Benefits and job satisfaction are the dimensions of job quality that are best correlated with not living in poverty.